Development of stromal differentiation patterns in heterotypical models of artificial corneas generated by tissue engineering - Blanco-Elices, Cristina; Morales-Álvarez, Carmen; Chato-Astrain, Jesús; González-Gallardo, Carmen; Ávila-Fernández, Paula; Campos, Fernando; Carmona, Ramón; Martín-Piedra, Miguel Ángel; Garzón, Ingrid; Alaminos, Miguel (Frontiers in Bioengineering and Biotechnology, 2023)
Purpose: We carried out a histological characterization analysis of the stromal layer of human heterotypic cornea substitutes generated with extra-corneal cells to determine their putative usefulness in tissue engineering. Methods: Human bioartificial corneas were generated using nanostructured fibrin-agarose biomaterials with corneal stromal cells immersed within. To generate heterotypical corneas, umbilical cord Wharton’s jelly stem cells (HWJSC) were cultured on the surface of the stromal substitutes to obtain an epithelial-like layer. These bioartificial corneas were compared with control native human corneas and with orthotypical corneas generated with human corneal epithelial cells on top of the stromal substitute. Both the corneal stroma and the basement membrane were analyzed using histological, histochemical and immunohistochemical methods in samples kept in culture and grafted in vivo for 12 months in the rabbit cornea. Results: Our results showed that the stroma of the bioartificial corneas kept ex vivo showed very low levels of fibrillar and non-fibrillar components of the tissue extracellular matrix. However, in vivo implantation resulted in a significant increase of the contents of collagen, proteoglycans, decorin, keratocan and lumican in the corneal stroma, showing higher levels of maturation and spatial organization of these components. Heterotypical corneas grafted in vivo for 12 months showed significantly higher contents of collagen fibers, proteoglycans and keratocan. When the basement membrane was analyzed, we found that all corneas grafted in vivo showed intense PAS signal and higher contents of nidogen-1, although the levels found in human native corneas was not reached, and a rudimentary basement membrane was observed using transmission electron microscopy. At the epithelial level, HWJSC used to generate an epithelial-like layer in ex vivo corneas were mostly negative for p63, whereas orthotypical corneas and heterotypical corneas grafted in vivo were positive. Conclusion: These results support the possibility of generating bioengineered artificial corneas using non-corneal HWJSC. Although heterotypical corneas were not completely biomimetic to the native human corneas, especially ex vivo, in vivo grafted corneas demonstrated to be highly biocompatible, and the animal cornea became properly differentiated at the stroma and basement membrane compartments. These findings open the door to the future clinical use of these bioartificial corneas.